BEDAH ALUR EKRANISASI NOVEL BUMI MANUSIA KARYA PRAMOEDYA ANANTA TOER KE DALAM FILM KARYA HANUNG BRAMANTYO - aqilla fadhia raihan; Ika Mustika; Dida Firmansyah (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Currently, literart works become a trend among all ages because of changes in form that add to the aesthetics of a literary work. Not infrequently a literary work becomes a film that is widely carried out by filmmakers. Most people choose to watch movies in the midst of their busy lives to calm their minds from various activites. This is further strengthened by the number of best-selling novels in the market which are converted into films. Whether youth novels, horror, even history, a novel can be turned into an interesting and worthy film to watch. In this study, researchers chose the novel Bumi Manusia by Pramoedya Ananta Toer and the film Bumi Manusia by director Hanung Bramantyo as research materials. The purpose of this study is to describe the process of ecranization of the plot, setting, character, both in terms of categories of shrinking, adding, and varying aspects in the transfer of the novel to the film form. Data is done by reading, then watching, then taking notes. The results show that the ecranization process occurs in the elements of the plot, setting, character, namely the existence of various shrinkage, additions and changes. As for the various changes that occur at the end of the scenes that seem to be accelerated by the omission of scenes in the novel. When the screening of the film does not deviate from the plot of the novel and these changes add to the content of the meaning of the film Bumi Manusia.